Time-course analysis of nuclear events during conjugation in the marine ciliate Euplotes vannus and comparison with other ciliates (Protozoa, Ciliophora) - Yaohan Jiang; Tengteng Zhang; Adriana Vallesi; Xianyu Yang; Feng Gao (Taylor & Francis, 2018)
Ciliates represent a morphologically and genetically distinct group of single-celled eukaryotes that segregate germline and somatic functions into two types of nuclei and exhibit complex cytogenetic events during the sexual process of conjugation, which is under the control of the so-called “mating type systems”. Studying conjugation in ciliates may provide insight into our understanding of the origins and evolution of sex and fertilization. In the present work, we studied in detail the sexual process of conjugation using the model species Euplotes vannus, and compared these nuclear events with those occurring in other ciliates. Our results indicate that in E. vannus: 1) conjugation requires about 75 hours to complete: the longest step is the development of the new macronucleus (ca. 64h), followed by the nuclear division of meiosis I (5h); the mitotic divisions usually take only 2h; 2) there are three prezygotic divisions (mitosis and meiosis I and II), and two of the eight resulting nuclei become pronuclei; 3) after the exchange and fusion of the pronuclei, two postzygotic divisions occur; two of the four products differentiate into the new micronucleus and macronucleus, respectively, and the parental macronucleus degenerates completely; 4) comparison of the nuclear events during conjugation in different ciliates reveals that there are generally three prezygotic divisions while the number of postzygotic divisions is highly variable. These results can serve as reference to investigate the mating type system operating in this species and to analyze genes involved in the different steps of the sexual process.
Keywords: Medicine; Cell Biology; Genetics; Physiology; Biological Sciences not elsewhere classified; Developmental Biology